Breslow Density Is a Novel Prognostic Feature That Adds Value to Melanoma Staging. (June 2018) - Saldanha, Gerald; Yarrow, Jeremy; Pancholi, Jay; Flatman, Katarina; Teo, Kah Wee; Elsheik, Somaia; Harrison, Rebecca; O'Riordan, Marie; Bamford, Mark
Abstract : Histomorphologic prognostic biomarkers that can be measured using only an hematoxylin and eosin stain are very attractive because they are simple and cheap. We conceived an entirely novel biomarker of this type, the Breslow density (BD), which measures invasive melanoma cell density at the site where Breslow thickness (BT) is measured. This study assessed BD's prognostic value. In this study, BD was measured in 1329 melanoma patients. Measurement accuracy and precision was assessed using intraclass correlation coefficient (ICC). Survival was assessed with a primary end-point of melanoma-specific survival (MSS) and also overall survival and metastasis-free survival. We found that BD measurement was accurate compared with gold standard image analysis (ICC, 0.84). Precision was excellent for 3 observers with different experience (ICC, 0.93) and for an observer using only written instructions (ICC, 0.93). BD was a highly significant predictor in multivariable analysis for overall survival, MSS, and metastasis-free survival (each, P <0.001) and it explained MSS better than BT, but BT and BD together had best explanatory capability. A BD cut point of ≥65% was trained in 970 melanomas and validated in 359. This cut point showed promise as a novel way to upstage melanoma from T stage "a" to "b." BD was combined with BT to create a targeted burden score. This was a validated as an adjunct to American Joint Committee on Cancer stage. In summary, BD can be measured accurately and precisely. It demonstrated independent prognostic value and explained MSS better than BT alone. Notably, we demonstrated ways that BD could be used with American Joint Committee on Cancer version 8 staging. Abstract : Supplemental Digital Content is available in the text.